A CASE OF UTERINE TORSION IN SHEEP - NAIDU, G VENKATA (The Indian Journal of Animal Reproduction, 2023)
A rare case of dystocia due to uterine torsion has been reported in a sheep.
Keywords: Sheep; Uterine torsion; Dystocia